Bayesian network analysis revealed the connectivity difference of the default mode network from the resting-state to task-state - Wu, Xia; Yu, Xinyu; Yao, Li; Li, Rui (Frontiers in Computational Neuroscience, 2014)
Functional magnetic resonance imaging (fMRI) studies have converged to reveal the default mode network (DMN), a constellation of regions that display co-activation during resting-state but co-deactivation during attention-demanding tasks in the brain. Here, we employed a Bayesian network (BN) analysis method to construct a directed effective connectivity model of the DMN and compared the organizational architecture and interregional directed connections under both resting-state and task-state. The analysis results indicated that the DMN was consistently organized into two closely interacting subsystems in both resting-state and task-state. The directed connections between DMN regions changed significantly from the resting-state to task-state condition. These results suggest that the DMN intrinsically maintains a relatively stable structure whether at rest or performing tasks but has different information processing mechanisms under varied states.